Pengaruh Media Pembelajaran dan Kemandirian Belajar Terhadap Hasil Belajar IPA Siswa Kelas IV Sekolah Dasar Negeri 1 Pengkelak Mas - Alimuddin, Alimuddin (khatulistiwa, 2020)
This study aims to determine the effect of the learning media including video and picture media and self-regulated learning of the learning outcomes of Natural Science on the content correlation between natural resources with environment and technology. The study was conducted on students in grade IV Sekolah Dasar Negeri 1 Pengkelak Mas, a number of students as many as 36 students. Research using experiment method treatment by level 2 x 2. Data analysis is the analysis of the variance of two paths (ANOVA). The result of this study indicates that (1) There are differences in learning outcomes of natural science among the group given video media and the group given picture media (2) there are interactions between learning media with self-regulated learning outcomes of natural science on the content correlation between natural resources with environment and technology.